Investing in green bonds and its impact on stock prices and profitability for banks A study of his analysis of a sample of Canadian banks, Royal Bank, as a model For the period (2005-2022) - Hameed, Hawraa Zaki; Alwan, Badir Mohammed; Ibraheem, Balassem Mohammed; Hussein, Haider Nasser (Technium Business and Management, 2023)
Investing in clean energy projects requires non-traditional tools, including green bonds, as they provide a set of advantages that qualify the projects to obtain financing. Therefore, this study aims to demonstrate the impact of Canadian banks introducing green bonds in their list of investments and the extent of their impact on the prices and returns of their shares. In the financial market , The study relied on the most important test for normal distribution, which is the Kolmogorov-Smirnov test, and a time series for a period of (18) years, from (2005 - 2022), as the bank did not deal in green bonds for the period (2005 - 2013), that is, for a period of (9) years. Green bonds were dealt with for the period (2014-2022), The results of the study showed that there was a clear increase in the stock price and its profitability after investing in green bonds over the previous period of this investment. In order to test the significance of this increase, the statistical program (Statgraphics V.18) was used.